TINGKAT KEMANDIRIAN BELAJAR SISWA KELAS XII SMK AL-HUDA BUMIAYU DI MASA PEMBELAJARAN DARING - Amanda Tasya Puspita; Dini Rakhmawati; Ismah Ismah (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
The Covid-19 pandemic then resulted in changes in the management of the education system in Indonesia. The government provides a policy to implement online learning so that the learning process can still be carried out. One of the objectives to be achieved from the research is to find out the high or low level of student learning independence during online learning. This research is a quantitative research with the type of descriptive survey research. The research population included all class XII students of SMK Al-Huda Bumiayu. Samples were taken by 106 students using the Saturated Sampling technique. In this study, data collection was carried out using a learning independence scale through google form. The results showed that 77.3% of students had a high level of learning independence, it could be seen from the preparation before taking part in learning such as making an additional study schedule to meet the learning targets achieved, making a summary of the material, studying the material from various references, assuming the task given by the teacher was a challenging challenge. must be resolved. When viewed from the gender of women tend to have high independence compared to men as many as 55 respondents. The conclusion of this research is that there is independent learning in the online learning period with a high category. Although all students are able to independently manage the learning process, there are still some students who are still unable to manage their learning time. The teacher is still the center of the learning process and dominates teaching and learning activities.